2013
DOI: 10.1302/0301-620x.95b12.31802
|View full text |Cite
|
Sign up to set email alerts
|

Controversies relating to the management of acromioclavicular joint dislocations

Abstract: The aim of this review is to address controversies in the management of dislocations of the acromioclavicular joint. Current evidence suggests that operative rather than non-operative treatment of Rockwood grade III dislocations results in better cosmetic and radiological results, similar functional outcomes and longer time off work. Early surgery results in better functional and radiological outcomes with a reduced risk of infection and loss of reduction compared with delayed surgery. Surgical options include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
68
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 40 publications
2
68
0
8
Order By: Relevance
“…Consequently, hook plate seems to be capable of anatomical reduction in superoinferior reduction even without coracoclavicular ligament reconstruction. Modi et al 10) reported that the goal of fixation of ACJ is to restore the CCD in order to allow healing of the ruptured ligaments. Also, Luis et al 26) reported that coracoclavicular ligament repair is unnecessary with hook plates because anatomical reduction is done.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, hook plate seems to be capable of anatomical reduction in superoinferior reduction even without coracoclavicular ligament reconstruction. Modi et al 10) reported that the goal of fixation of ACJ is to restore the CCD in order to allow healing of the ruptured ligaments. Also, Luis et al 26) reported that coracoclavicular ligament repair is unnecessary with hook plates because anatomical reduction is done.…”
Section: Discussionmentioning
confidence: 99%
“…9) Its use has increased since the advent of locking plate with locking screws and good results are being reported. 10,11) But there are few reports comparing the clinical outcomes of these two techniques, and there is no report comparing two techniques in Korea. The purpose of this study is to use K-wire transfixation and locking hook plate fixation technique for ACJ stabilization in acute ACJ dislocation patients and retrospectively compare the clinical and radiologic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…19,20) However, there are known disadvantages associated with this technique, including a mandatory second surgery for removal of the plate. Moreover, transarticular fixation using an HP may induce bony osteolysis, shoulder impingement, and rotator cuff damage, leading to poor functional results.…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition, all of these implants require removal. The more recent trend toward tunnel and suture-graft fixation appears promising, but direct comparison of different techniques is difficult because multiple variables exist, including the use of 1 versus 2 tunnels, graft versus suture, allograft versus autograft, and adjustable-length suture versus nonadjustable suture.…”
Section: Discussionmentioning
confidence: 99%
“…Management of grade III separations remains controversial. 1 Multiple operative techniques for these injuries have been described. More historical methods of fixation include Kirschner wires, hook plates, and use of a coracoclavicular screw.…”
mentioning
confidence: 99%